Taking Stock of the UNFCCC Process and its Inter-linkages - Briner, Gregory (OECD Publishing, 2014)
Governments are currently negotiating the elements of a new climate change agreement to be adopted at the forthcoming COP 21 conference in Paris in 2015. The aim of this paper is to take stock of existing UNFCCC institutions and arrangements and the inter-linkages between them in the areas of mitigation, adaptation and loss and damage, means of implementation, and measurement, reporting and verification (MRV), with a view to informing discussions on the possible elements of a 2015 agreement. A pragmatic agreement would focus on using existing institutions and arrangements more effectively, before creating new ones. Some institutions and arrangements have been established only recently, and time is needed before their effectiveness can be fairly assessed
Keywords: Energy; Environment